Dose and Time Dependence of Targeted and Untargeted Effects after Very Low doses of α-Particle Irradiation of Human Lung Cancer Cells - A. Belchior; O. Monteiro Gil; P. Almeida; P. Vaz (SAGE Publishing, 2013)
Understanding the effects to human health resulting from exposure to low doses of ionizing radiation is a persisting challenge. No one questions the deleterious consequences for humans following exposure to high radiation doses; however, in the low dose range, the complex and to some extent unknown cellular responses raise important misgivings about the resulting protective or potentially detrimental effects. Bystander effects are involved in low dose exposures, being characterized by the appearance in unirradiated cells of a cellular damage associated with direct radiation exposure. The purpose of our work was to assess, by using clonogenic and micronuclei assays, the dose and time dependence of the bystander response after cells exposure to very low doses of α-particles and to evaluate its importance in the overall induced damage. The study includes an irradiated cells culture, a medium transfer culture with non-irradiated cells and a culture with irradiated cells after centrifugation. We observed a non-negligible contribution of the bystander effects in the overall cellular damage. Low-dose hyper-sensitivity was observed for medium transfer and irradiated cells after centrifugation cultures. Delayed and earlier cellular damage were similar in almost all experiments, suggesting an effectiveness of irradiated medium to induce a bystander response soon after irradiation.